Flame-retardant plastic containing carbon nanotubes and preparation method of flame-retardant plastic

By introducing carbon nanotubes and composite flame retardant into PET plastics, combining the synergistic effects of kaolin and nanomagnesium hydroxide film layers, the problem of insufficient mechanical and flame retardant performance of existing PET plastics is solved, and excellent flame retardant is achieved Performance and electromagnetic shielding effect improve the overall quality of the product.

CN119177007APending Publication Date: 2024-12-24GUANGDONG PULAI NANO NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444057.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The mechanical properties and flame retardant properties of existing high-temperature antibacterial PET plastics are insufficient, which affects their quality and quality.

Method used

Using a flame retardant plastic formula containing carbon nanotubes, a porous structure is formed by calcining kaolin at high temperature, a nanomagnesium hydroxide film layer is deposited, and a composite flame retardant is prepared to improve flame retardant performance, combined with tris(xylene) phosphate Synergistically, it forms plastic with excellent flame retardant properties.

Benefits of technology

It significantly improves the mechanical properties, electromagnetic shielding properties and flame retardant properties of plastics, ensures the quality and quality of the products, and is suitable for many high-tech fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005087191700000031
    Figure BDA0005087191700000031
  • Figure BDA0005087191700000051
    Figure BDA0005087191700000051
  • Figure BDA0005087191700000071
    Figure BDA0005087191700000071
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to flame-retardant plastic containing carbon nanotubes and a preparation method of the flame-retardant plastic. The flame-retardant plastic containing the carbon nanotubes is prepared from the following raw materials in parts by weight: 100 to 120 parts of PET (Polyethylene Terephthalate) resin, 20 to 30 parts of ABS (Acrylonitrile Butadiene Styrene) resin, 3 to 6 parts of triethanolamine, 4 to 6 parts of the carbon nanotubes, 3 to 5 parts of tris (xylene) phosphate, 2 to 4 parts of pentaerythritol stearate, 5 to 8 parts of nano powder, 0.8 to 2 parts of antioxidant, 2 to 5 parts of compatilizer, 1 to 2 parts of ultraviolet screening agent and 5 to 8 parts of compound flame retardant, the plastic product prepared by the invention not only has excellent mechanical property and electromagnetic shielding property, but also has excellent flame retardant property, and the quality of the plastic product is effectively ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a flame retardant plastic containing carbon nanotubes and a preparation method thereof. Background Art

[0002] Plastic refers to a plastic (flexible) material formed by processing with a high molecular weight synthetic resin as the main component, and adding appropriate additives such as plasticizers, stabilizers, antioxidants, flame retardants, colorants, etc., or a rigid material formed by curing and cross-linking. With the development of the plastics industry, plastics have become an indispensable new material for technological transformation, promoting technological progress and developing high-tech products in the fields of automobiles, aerospace, electronics and electrical, packaging, building materials, agriculture, etc. As a one-dimensional nanomaterial, carbon nanotubes are light in weight, have a perfectly connected hexagonal structure, and have many abnormal mechanical, electrical and chemical properties. The P electrons of its carbon atoms form a large range of delocalized π bonds. Due to the significant conjugation effect, carbon nanotubes have excellent electrical conductivity. If carbon nanotubes are added in the process of preparing plastics, it can not only effectively improve its mechanical properties and electrical conductivity, but also effectively improve its electromagnetic shielding performance and reduce the interference caused by external electromagnetics.

[0003] In the patent document with application number "CN202310733422.9", "a kind of high temperature resistant antibacterial PET plastic and its preparation method" is disclosed. The high temperature resistant antibacterial PET plastic is prepared by the following raw materials by weight: 100-200 parts of PET resin, 30-50 parts of PBT resin, 1-3 parts of chain extender, 20-30 parts of porous alumina antibacterial microspheres, 3-7 parts of carbon fiber, 2-5 parts of microcrystalline cellulose, 1-4 parts of compatibilizer, 1-3 parts of lubricant and 2-5 parts of antioxidant. Although the PET plastic prepared by this patent document has good high temperature resistance and antibacterial properties, its own mechanical properties and flame retardant properties are relatively insufficient, which affects its quality to a certain extent. Therefore, the present invention provides a flame-retardant plastic containing carbon nanotubes and a preparation method thereof to solve the above-mentioned technical problems! Summary of the invention

[0004] The purpose of the present invention is to provide a flame retardant plastic containing carbon nanotubes and a preparation method thereof. The prepared plastic product not only has excellent mechanical properties and electromagnetic shielding properties, but also has excellent flame retardant properties, effectively ensuring its quality.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A flame retardant plastic containing carbon nanotubes, comprising the following raw materials in parts by weight: 100-120 parts of PET resin, 20-30 parts of ABS resin, 3-6 parts of triethanolamine, 4-6 parts of carbon nanotubes, 3-5 parts of tri(xylene) phosphate, 2-4 parts of pentaerythritol stearate, 5-8 parts of nano powder, 0.8-2 parts of antioxidant, 2-5 parts of compatibilizer, 1-2 parts of anti-ultraviolet agent and 5-8 parts of compound flame retardant; wherein,

[0007] The ABS resin has a molecular weight of 80,000 to 150,000, and includes 5 to 30% by mass of butadiene, 10 to 30% by mass of acrylonitrile, and 40 to 70% by mass of styrene;

[0008] The molecular weight of the PET resin is 20,000 to 30,000, and the melt index measured at 190° C. and 21.6 kg according to GB-T3682 is 300 g / 10 min to 600 g / 10 min.

[0009] Furthermore, the nano powder is compounded by nano titanium dioxide and nano silicon dioxide in a mass ratio of 1:0.8 to 1.2.

[0010] Furthermore, the antioxidant is selected from any one of antioxidant 1010, antioxidant 168, and antioxidant 1076.

[0011] Furthermore, the compatibilizer is POE-g-MAH, and the maleic anhydride grafting rate thereof is 0.8-2.5%.

[0012] Furthermore, the anti-ultraviolet agent is selected from any one of anti-ultraviolet agent UV-531, anti-ultraviolet agent UV-326, and anti-ultraviolet agent UV-328.

[0013] Furthermore, the preparation method of the composite flame retardant comprises the following steps:

[0014] Step 1, adding the organic compound into an ethanol aqueous solution with a volume concentration of 60-85% at a dosage ratio of 0.1-0.3 g / mL, stirring and mixing evenly, heating to 30-50° C., and ultrasonically treating at this temperature for 20-40 minutes, and after the ultrasonic treatment is completed, the obtained grafting agent is obtained;

[0015] Wherein, the structure of the organic compound is as follows:

[0016]

[0017] Step 2: Add the inorganic substrate into a mixed solvent at a solid-liquid ratio of 0.01 to 0.02 g / mL, and then slowly add a grafting agent whose mass is 2 to 4 times that of the inorganic substrate. After the addition is completed, the temperature of the obtained mixed component is raised to 50 to 70°C, and the mixture is stirred and reacted at this temperature for 10 to 20 hours; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then solid-liquid separation and vacuum drying are carried out in sequence to obtain a composite flame retardant; wherein the mixed solvent is prepared by mixing DMF and ethanol whose volume is 1 to 2 times that of DMF.

[0018] Furthermore, the preparation method of the inorganic substrate is: calcined kaolin is added to a 0.1-0.3 g / mL magnesium sulfate aqueous solution at a solid-liquid ratio of 0.02-0.05 g / mL, and after mixing and stirring evenly, the temperature of the resulting mixed solution is raised to 70-90°C, and at this temperature, slaked lime with a mass of 65-75% of magnesium sulfate is added thereto while stirring, and after stirring the reaction for 2-4 hours, the resulting product components are sequentially subjected to solid-liquid separation, washing, vacuum drying, and depolymerization and dispersion treatment to obtain an inorganic substrate.

[0019] Furthermore, the preparation method of the calcined kaolin is: transfer the kaolin into a calcination device and calcine it at a temperature of 750-880°C for 4-6 hours; after the calcination is completed, grind it and pass it through a 200-300 mesh sieve to obtain the calcined kaolin.

[0020] Furthermore, the carbon nanotubes are multi-walled carbon nanotubes with an inner diameter of 6-10 nm, an outer diameter of 30-50 nm, and an aspect ratio of 5-20.

[0021] A method for preparing a flame-retardant plastic containing carbon nanotubes comprises the following steps:

[0022] The first step is to weigh each raw material according to the formula, and then dry the PET resin and ABS resin at a temperature of 75-85°C for 2-3 hours and store them for standby use;

[0023] Step 2: Add the dried PET resin and ABS resin into a high-speed mixer and mix and stir at a rate of 600-800 r / min for 5-10 min, then add the remaining raw materials and continue to mix and stir at a rate of 1500-2000 r / min for 20-30 min;

[0024] The third step is to transport the obtained mixed slurry to a twin-screw extruder after the mixing is complete, and to perform melt extrusion granulation at a temperature of 235-255° C., and the final product is a flame-retardant plastic product containing carbon nanotubes.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] In the present invention, kaolin is used as a starting material, and calcined at high temperature to form calcined kaolin with a porous structure, thereby increasing its specific surface area and enhancing its load capacity, laying a foundation for the subsequent deposition of a nano-magnesium hydroxide film layer. The obtained calcined kaolin is put into a magnesium sulfate aqueous solution, and then slaked lime is added thereto, and finally a dense nano-magnesium hydroxide film layer is deposited on the surface of the kaolin with a porous structure, and then the inorganic substrate is obtained after solid-liquid separation, washing, vacuum drying and depolymerization and dispersion treatment in sequence, and the presence of the nano-magnesium hydroxide film layer effectively improves the flame retardant performance of the calcined kaolin.

[0027] Furthermore, in the present invention, an organic compound is put into an ethanol aqueous solution and subjected to ultrasonic treatment to hydrolyze it so as to prepare a grafting agent. Then, an inorganic substrate is put into a mixed solvent and a grafting agent is slowly added thereto. The grafting agent reacts chemically with the active groups on the surface of the inorganic substrate through a heat preservation and stirring reaction. Finally, the grafting agent is effectively grafted on the surface of the inorganic substrate through chemical bonds to prepare a composite flame retardant. Under the synergistic effect of the grafting agent in the outermost layer, the nano magnesium hydroxide film layer in the second outer layer and the core layer calcined kaolin, the composite flame retardant with a "core-shell" structure has excellent flame retardant properties. It cooperates with tri(xylene) phosphate and cooperates with each other to effectively ensure the flame retardant properties of the prepared plastic product. In addition, the plastic product prepared by the present invention also has excellent mechanical properties and electromagnetic shielding properties, reduces the interference caused by external electromagnetics, and effectively ensures its quality. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A flame retardant plastic containing carbon nanotubes, comprising the following raw materials in parts by weight: 100 parts of PET resin, 20 parts of ABS resin, 3 parts of triethanolamine, 4 parts of carbon nanotubes, 3 parts of tri(xylene) phosphate, 2 parts of pentaerythritol stearate, 5 parts of nano powder, 0.8 parts of antioxidant 1010, 2 parts of compatibilizer, 1 part of anti-ultraviolet agent UV-531 and 5 parts of compound flame retardant; wherein,

[0031] The molecular weight of the ABS resin is 80,000, and it includes 5 to 30% by mass of butadiene, 10 to 30% by mass of acrylonitrile, and 40 to 70% by mass of styrene;

[0032] The molecular weight of PET resin is 20000, and the melt index measured at 190°C and 21.6Kg according to GB-T3682 is 300g / 10min;

[0033] The nano powder is compounded by nano titanium dioxide and nano silicon dioxide in a mass ratio of 1:0.8; POE-g-MAH is selected as the compatibilizer, and its maleic anhydride grafting rate is 1.5%; the carbon nanotube is a multi-walled carbon nanotube with an inner diameter of 6nm, an outer diameter of 30nm and an aspect ratio of 5.

[0034] The preparation method of the compound flame retardant comprises the following steps:

[0035] Step 1: adding the organic compound into a 60% ethanol aqueous solution at a dosage ratio of 0.1 g / mL, stirring and mixing evenly, heating to 30° C., and ultrasonically treating at this temperature for 20 minutes. After the ultrasonic treatment is completed, the obtained product is a grafting agent;

[0036] Among them, the structure of organic compounds is as follows:

[0037]

[0038] Step 2: Add the inorganic substrate into the mixed solvent at a solid-liquid ratio of 0.01 g / mL, and then slowly add a grafting agent with a mass twice that of the inorganic substrate. After the addition is completed, the temperature of the obtained mixed components is raised to 50°C, and the mixture is stirred and reacted at this temperature for 10 hours; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then subjected to solid-liquid separation and vacuum drying in sequence to obtain a composite flame retardant; wherein the mixed solvent is prepared by mixing equal volumes of DMF and ethanol.

[0039] The preparation method of the inorganic substrate is as follows: calcined kaolin is added to a 0.1 g / mL magnesium sulfate aqueous solution at a solid-liquid ratio of 0.02 g / mL, the mixture is stirred evenly, the temperature of the resulting mixture is raised to 70°C, and at this temperature, slaked lime with a mass ratio of 65% of magnesium sulfate is added thereto while stirring, and after stirring for 2 hours, the resulting product components are sequentially subjected to solid-liquid separation, washing, vacuum drying, and depolymerization and dispersion treatment to obtain the inorganic substrate.

[0040] The preparation method of calcined kaolin is as follows: transfer kaolin into calcination equipment and calcine at a temperature of 750°C for 4 hours; after calcination is completed, grind and pass through a 200-mesh sieve in sequence to obtain calcined kaolin.

[0041] A method for preparing a flame-retardant plastic containing carbon nanotubes comprises the following steps:

[0042] The first step is to weigh each raw material according to the formula, and then dry the PET resin and ABS resin at 75°C for 3 hours and store them for standby use;

[0043] Step 2: Add the dried PET resin and ABS resin into a high-speed mixer and mix and stir at a rate of 600 r / min for 10 min, then add the remaining raw materials and continue to mix and stir at a rate of 1500 r / min for 30 min;

[0044] The third step is to transport the obtained mixed slurry to a twin-screw extruder after the mixing is complete, and to perform melt extrusion granulation at a temperature of 235° C. The final product is a flame-retardant plastic product containing carbon nanotubes.

[0045] Example 2

[0046] The method for preparing a flame-retardant plastic containing carbon nanotubes provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the raw materials used for the flame-retardant plastic and the preparation method of the compound flame retardant are not completely the same, and the specific composition of the raw materials used for the flame-retardant plastic and the preparation method of the compound flame retardant in this embodiment are as follows:

[0047] A flame-retardant plastic containing carbon nanotubes is composed of the following raw materials in parts by weight: 110 parts of PET resin, 25 parts of ABS resin, 4 parts of triethanolamine, 5 parts of carbon nanotubes, 4 parts of tri(xylene) phosphate, 3 parts of pentaerythritol stearate, 6 parts of nano powder, 1.5 parts of antioxidant 168, 3 parts of POE-g-MAH compatibilizer, 1.5 parts of anti-ultraviolet agent UV-326 and 6 parts of compound flame retardant; wherein the nano powder is compounded by nano titanium dioxide and nano silicon dioxide of equal weight.

[0048] The preparation method of the compound flame retardant comprises the following steps:

[0049] Step 1, adding the organic compound in a dosage ratio of 0.2 g / mL into an ethanol aqueous solution with a volume concentration of 75%, stirring and mixing evenly, heating to 40° C., and ultrasonically treating at this temperature for 30 minutes, and after the ultrasonic treatment is completed, the obtained product is a grafting agent;

[0050] Among them, the structure of organic compounds is as follows:

[0051]

[0052] Step 2: Add the inorganic substrate into the mixed solvent at a solid-liquid ratio of 0.015 g / mL, and then slowly add a grafting agent with a mass 3 times that of the inorganic substrate. After the addition is completed, the temperature of the obtained mixed components is raised to 60°C, and the mixture is stirred and reacted at this temperature for 15 hours; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then subjected to solid-liquid separation and vacuum drying in sequence to obtain a composite flame retardant; wherein the mixed solvent is prepared by mixing equal volumes of DMF and ethanol.

[0053] The preparation method of the inorganic substrate is as follows: calcined kaolin is added to a 0.2 g / mL magnesium sulfate aqueous solution at a solid-liquid ratio of 0.03 g / mL, the mixture is stirred evenly, the temperature of the resulting mixture is raised to 80°C, and at this temperature, slaked lime with a mass of 70% of the magnesium sulfate is added thereto while stirring, the reaction is stirred for 3 hours, and the resulting product components are sequentially subjected to solid-liquid separation, washing, vacuum drying, and depolymerization and dispersion treatment to obtain the inorganic substrate.

[0054] The preparation method of calcined kaolin is as follows: transfer the kaolin into a calcination device and calcine it at a high temperature of 800°C for 5 hours; after the calcination is completed, grind it and pass it through a 250-mesh sieve in sequence to obtain the calcined kaolin.

[0055] Example 3

[0056] The method for preparing a flame-retardant plastic containing carbon nanotubes provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the raw materials used for the flame-retardant plastic and the preparation method of the compound flame retardant are not completely the same, and the specific composition of the raw materials used for the flame-retardant plastic and the preparation method of the compound flame retardant in this embodiment are as follows:

[0057] A flame retardant plastic containing carbon nanotubes is composed of the following raw materials in parts by weight: 120 parts of PET resin, 30 parts of ABS resin, 6 parts of triethanolamine, 6 parts of carbon nanotubes, 5 parts of tri(xylene) phosphate, 4 parts of pentaerythritol stearate, 8 parts of nano powder, 2 parts of antioxidant 1076, 5 parts of POE-g-MAH compatibilizer, 2 parts of anti-ultraviolet agent UV-328 and 8 parts of compound flame retardant; wherein the nano powder is compounded by nano titanium dioxide and nano silicon dioxide in a mass ratio of 1:1.2.

[0058] The preparation method of the compound flame retardant comprises the following steps:

[0059] Step 1, adding the organic compound in a dosage ratio of 0.3 g / mL into an ethanol aqueous solution with a volume concentration of 85%, mixing and stirring evenly, heating to 50° C., and ultrasonically treating at this temperature for 40 minutes, and after the ultrasonic treatment is completed, the obtained product is a grafting agent;

[0060] Among them, the structure of organic compounds is as follows:

[0061]

[0062] Step 2: Add the inorganic substrate into the mixed solvent at a solid-liquid ratio of 0.02 g / mL, and then slowly add a grafting agent with a mass that is 4 times that of the inorganic substrate. After the addition is completed, the temperature of the obtained mixed components is raised to 70°C, and the mixture is stirred and reacted at this temperature for 20 hours; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then subjected to solid-liquid separation and vacuum drying in sequence to obtain a composite flame retardant; wherein the mixed solvent is prepared by mixing DMF and ethanol with a volume that is twice that of the DMF.

[0063] The preparation method of the inorganic substrate is as follows: calcined kaolin is added to a 0.3 g / mL magnesium sulfate aqueous solution at a solid-liquid ratio of 0.05 g / mL, the mixture is stirred evenly, the temperature of the resulting mixture is raised to 90°C, and at this temperature, slaked lime with a mass of 75% of magnesium sulfate is added thereto while stirring, and after stirring for 4 hours, the resulting product components are sequentially subjected to solid-liquid separation, washing, vacuum drying, and depolymerization and dispersion treatment to obtain the inorganic substrate.

[0064] The preparation method of calcined kaolin is as follows: transfer kaolin into calcination equipment and calcine at a temperature of 880°C for 6 hours; after calcination is completed, grind and pass through a 300-mesh sieve in sequence to obtain calcined kaolin.

[0065] Comparative Example 1: The main difference between this example and Example 1 is that an equal amount of inorganic base material is used in this example to replace the compound flame retardant.

[0066] Comparative Example 2: The main difference between this example and Example 1 is that an equal amount of tri(xylene) phosphate is used in this example to replace the compound flame retardant.

[0067] Comparative Example 3: The main difference between this embodiment and embodiment 1 is that an equal amount of a compound flame retardant is used in this embodiment to replace tri(xylene) phosphate.

[0068] Performance Testing

[0069] The relevant properties of the flame retardant plastic products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively, and the obtained test data were recorded in the following table:

[0070]

[0071]

[0072] By comparing and analyzing the relevant data in the table, it can be seen that the plastic product prepared by the present invention not only has excellent mechanical properties and electromagnetic shielding properties, reducing the interference caused by external electromagnetics, but also has excellent flame retardant properties, effectively ensuring its quality. This shows that the flame retardant plastic containing carbon nanotubes and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0073] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0074] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A flame retardant plastic containing carbon nanotubes, characterized in that: It is composed of the following raw materials in parts by weight: 100-120 parts of PET resin, 20-30 parts of ABS resin, 3-6 parts of triethanolamine, 4-6 parts of carbon nanotubes, 3-5 parts of tri(xylene) phosphate, 2-4 parts of pentaerythritol stearate, 5-8 parts of nano powder, 0.8-2 parts of antioxidant, 2-5 parts of compatibilizer, 1-2 parts of anti-ultraviolet agent and 5-8 parts of compound flame retardant; wherein, The ABS resin has a molecular weight of 80,000 to 150,000 and includes 5 to 30% by mass of butadiene, 10 to 30% by mass of acrylonitrile, and 40 to 70% by mass of styrene; The molecular weight of the PET resin is 20,000 to 30,000, and the melt index measured at 190° C. and 21.6 kg according to GB-T3682 is 300 g / 10 min to 600 g / 10 min.

2. The flame-retardant plastic containing carbon nanotubes according to claim 1, characterized in that: The nanometer powder is compounded by nanometer titanium dioxide and nanometer silicon dioxide in a mass ratio of 1:0.8-1.

2.

3. The flame-retardant plastic containing carbon nanotubes according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 1010, antioxidant 168, and antioxidant 1076.

4. The flame-retardant plastic containing carbon nanotubes according to claim 1, characterized in that: The compatibilizer is POE-g-MAH, and the maleic anhydride grafting rate thereof is 0.8-2.5%.

5. The flame-retardant plastic containing carbon nanotubes according to claim 1, characterized in that: The anti-ultraviolet agent is selected from any one of anti-ultraviolet agent UV-531, anti-ultraviolet agent UV-326 and anti-ultraviolet agent UV-328.

6. The flame-retardant plastic containing carbon nanotubes according to claim 1, characterized in that: The preparation method of the composite flame retardant comprises the following steps: Step 1, adding the organic compound into an ethanol aqueous solution with a volume concentration of 60-85% at a dosage ratio of 0.1-0.3 g / mL, stirring and mixing evenly, heating to 30-50° C., and ultrasonically treating at this temperature for 20-40 minutes, and after the ultrasonic treatment is completed, the obtained grafting agent is obtained; Wherein, the structure of the organic compound is as follows: Step 2: Add the inorganic substrate into a mixed solvent at a solid-liquid ratio of 0.01 to 0.02 g / mL, and then slowly add a grafting agent whose mass is 2 to 4 times that of the inorganic substrate. After the addition is completed, the temperature of the obtained mixed component is raised to 50 to 70°C, and the mixture is stirred and reacted at this temperature for 10 to 20 hours; after the reaction is completed, the obtained product components are naturally cooled to room temperature, and then solid-liquid separation and vacuum drying are carried out in sequence to obtain a composite flame retardant; wherein the mixed solvent is prepared by mixing DMF and ethanol whose volume is 1 to 2 times that of DMF.

7. The flame retardant plastic containing carbon nanotubes according to claim 6, characterized in that: The preparation method of the inorganic substrate is as follows: calcined kaolin is added to a 0.1-0.3 g / mL magnesium sulfate aqueous solution at a solid-liquid ratio of 0.02-0.05 g / mL, the mixture is stirred evenly, the temperature of the resulting mixed solution is raised to 70-90° C., and at this temperature, slaked lime having a mass of 65-75% of magnesium sulfate is added thereto while stirring, the reaction is stirred for 2-4 hours, and the resulting product components are sequentially subjected to solid-liquid separation, washing, vacuum drying, and depolymerization and dispersion treatment to obtain the inorganic substrate.

8. The flame retardant plastic containing carbon nanotubes according to claim 7, characterized in that: The preparation method of the calcined kaolin is as follows: the kaolin is transferred into a calcining device and calcined at a temperature of 750-880°C for 4-6 hours; after the calcination is completed, the calcined kaolin is obtained by grinding and passing through a 200-300 mesh sieve.

9. The flame-retardant plastic containing carbon nanotubes according to claim 1, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes with an inner diameter of 6-10 nm, an outer diameter of 30-50 nm and an aspect ratio of 5-20.

10. A method for preparing a flame-retardant plastic containing carbon nanotubes according to any one of claims 1 to 9, characterized in that: The following steps are involved: The first step is to weigh each raw material according to the formula, and then dry the PET resin and ABS resin at a temperature of 75-85°C for 2-3 hours and store them for standby use; Step 2: Add the dried PET resin and ABS resin into a high-speed mixer and mix and stir at a rate of 600-800 r / min for 5-10 min, then add the remaining raw materials and continue to mix and stir at a rate of 1500-2000 r / min for 20-30 min; The third step is to transport the obtained mixed slurry to a twin-screw extruder after the mixing is complete, and to perform melt extrusion granulation at a temperature of 235-255° C., and the final product is a flame-retardant plastic product containing carbon nanotubes.